Outcome of Antimicrobial Therapy of Pediatric Urinary Tract Infections Caused by Extended-Spectrum β-Lactamase-Producing Enterobacteriaceae - Lee, Bongjin (The Korean Society of Infectious Diseases and Korean Society for Chemotherapy, 2013)
BACKGROUND: The purpose of this study was to compare the outcome of carbapenem versus non-carbapenem antimicrobial therapy for pediatric urinary tract infections (UTIs) caused by extended-spectrum β-lactamase (ESBL) producing Enterobacteriaceae. MATERIALS AND METHODS: From 2006 to 2011, 42 episodes of UTI caused by ESBL-producing Enterobacteriaceae were diagnosed at Seoul National University Children's Hospital. Patients were grouped according to the antimicrobials they received into a carbapenem group and a non-carbapenem group. Medical records were retrospectively reviewed to assess treatment outcome, time to defervescence after initiation of treatment, and relapse rate. RESULTS: There were 36 children with 42 episodes of UTI caused by ESBL-producing Enterobacteriaceae. Twenty-seven cases (64%) had an underlying urologic disease, 28 (67%) cases were caused by Escherichia coli, and 14 (33%) cases were caused by Klebsiella pneumoniae. Four (10%) cases were treated with carbapenem, 23 cases (55%) were treated with non-carbapenem, and 15 (36%) cases were treated by switching from a carbapenem to a non-carbapenem and vice versa. There was no treatment failure at the time of antimicrobial discontinuation. Between the carbapenem and the non-carbapenem treatment groups, there were no significant differences in bacterial etiology (P = 0.59), time to defervescence after the initiation of antimicrobials (P = 0.28), and relapse rate (P = 0.50). In vitro susceptibility to non-carbapenem antimicrobials did not affect the time to defervescence after the initiation of antimicrobial treatment, and the relapse rate in the non-carbapenem group. CONCLUSIONS: This study found no significant difference in the treatment outcome between pediatric patients treated with carbapenem and those treated with non-carbapenem antimicrobials for UTI caused by ESBL-producing Enterobacteriaceae. Therefore, the initially administered non-carbapenem can be maintained in UTI patients showing clinical improvement.